Revisiting English for Specific Purposes (ESP) in Indonesian Vocational High School (VHS): A Current Situation in Curriculum 2013 - Annisa Ratna Purwanti (Universitas PGRI Semarang, 2018)
This qualitative study tries to revisit the concept of ESP in VHS under the latest curriculum applied in Indonesia; curriculum 2013 or K-13. The researcher discovers current issues and several suggestions of ESP in Indonesian VHS context. Theoretically, English in VHS should employ ESP approach, but practically, it tends to be more general. The vague concept of ESP in the Indonesian VHS is one of the reasons in developing this study. On the other hand, government with its purpose of AEC (ASEAN Economic Community) eagers to make VHS students ready to work to compete with the foreign workers. However, since the implementation of K-13, English in VHS tends to have more general topics rather than in the previous curriculum (KTSP; curriculum 2006). As a result, it makes the concept of ESP in VHS more vague. The result of document analysis and observation, the researcher found several issues dealing with ESP. They are issues in course design, ESP teachers, ESP objectives, approach, and materials, and also learning assessment. Considering the major issues dealing with ESP in VHS, several countermeasures about redesign of ESP teaching in Indonesian VHS were suggested by the researcher.